PENGEMBANGAN KARIR TENAGA PENDIDIK DI SMP NEGERI 6 KOTA PARIAMAN - Telaumbanua, Irmansyah Putra; Sermal, Sermal; Nursyamsi, Nursyamsi (UIN Imam Bonjol Padang, 2023)
This research is motivated by problems related to the lack of career development activities for educators in schools, low motivation for educators for career development, low number of educators participating in career development activities, the need to increase educators' knowledge about academics, the need to increase teachers' mastery of IT. The research used qualitative methods with data collection techniques through observation, interviews and documentation. The data analysis technique in this research is by data reduction, data presentation, and drawing conclusions. The results of this research are the career development assignments for teaching staff in assignments at SMP Negeri 6 Kota Pariaman including: a) Teaching assignments. The criteria for assigning a teacher are seen from the teaching load of a minimum of 24 hours and a maximum of 40 faceto-face hours in one week. And must be in accordance with the academic qualification background held. The terms of a teacher's assignment include designing learning, implementing the learning process, and ending with evaluating learning outcomes; and b) Additional duties in the form of positions as deputy principal in various fields, head of laboratory, head of library, extracurricular supervisor, as well as class teacher, project coordinator, project teacher, scout teacher, scout supervisor, UKS supervisor, PMR supervisor, and OSIS supervisor